DNA topology influences p53 sequence-specific DNA binding through structural transitions within the target sites - Jagelská, Eva B; Brázda, Václav; Pecinka, Petr; Palecek, Emil; Fojta, Miroslav (The Biochemical journal, 2008)
The tumour suppressor protein p53 is one of the most important factors regulating cell proliferation, differentiation and programmed cell death in response to a variety of cellular stress signals. P53 is a nuclear phosphoprotein and its biochemical function is closely associated with its ability to bind DNA in a sequence-specific manner and operate as a transcription factor. Using a competition assay, we investigated the effect of DNA topology on the DNA binding of human wild-type p53 protein. We prepared sets of topoisomers of plasmid DNA with and without p53 target sequences, differing in their internal symmetry. Binding of p53 to DNA increased with increasing negative superhelix density (-sigma). At -sigma < or = 0.03, the relative effect of DNA supercoiling on protein-DNA binding was similar for DNA containing both symmetrical and non-symmetrical target sites. On the other hand, at higher -sigma, target sites with a perfect inverted repeat sequence exhibited a more significant enhancement of p53 binding as a result of increasing levels of negative DNA supercoiling. For -sigma = 0.07, an approx. 3-fold additional increase in binding was observed for a symmetrical target site compared with a non-symmetrical target site. The p53 target sequences possessing the inverted repeat symmetry were shown to form a cruciform structure in sufficiently negative supercoiled DNA. We show that formation of cruciforms in DNA topoisomers at -sigma > or = 0.05 correlates with the extra enhancement of p53-DNA binding.
Keywords: nádorový supresorový protein p53; Spodoptera; kultivované buňky; konformace nukleové kyseliny; Nucleic Acid Conformation; Protein Binding; repetitivní sekvence nukleových kyselin; DNA; Transition Temperature; DNA Topoisomerases, Type I; Tumor Suppressor Protein p53; Models, Biological; Repetitive Sequences, Nucleic Acid; Cells, Cultured; responzivní elementy; zvířata; Humans; superhelikální DNA; Binding Sites; DNA, Superhelical; DNA-topoisomerasy I; vazba proteinů; biologické modely; Response Elements; vazebná místa; lidé; tranzitní teplota; Animals